Una finestra sulla psichiatria tedesca. Comunicare nell’acuzie psichiatrica Appunti su ciò che aiuta o non aiuta le persone coinvolte - Struck, Ilka (Il sogno della farfalla, 2014)
The author, who has undergone hospital psychiatric treatment as a result of a schizoaffective disorder, uses her “clinical case” to highlight some problematic elements in the acute phase. She stresses the importance for staff members not to consider people in crisis as mere bearers of clinical symptoms, but as human beings who have their complex biography. The latter must also be addressed regarding any decisions taken that will affect them. On the basis of a number of specific episodes, the author illustrates which attitudes and which forms of behavior manifested by the nursing staff can allow for real communication even during a serious crisis.